python - How to rearrange sympy expressions containing a relational operator -
i have expressions containing relational operator, symbols, , constants. i'd rearrange expressions (to extent possible) constant terms on 1 side of relational operator, , remaining terms on other side. example, i'd rearrange:
x - 5 > y - z
to:
x - y + z > 5
is there existing sympy method doing this? if not, should start in extending sympy?
somewhat surprisingly, couldn't find way "out of box". can use method in this question make 1 variable sole subject of left hand side (lhs) of inequality can't seem make constant term subject.
so, wrote own version , reproduce below. i've tested on example given , couple of other examples. tries make right hand side (rhs) consist of either 0 or constant terms based on optional parameter. there may corner cases fails - use / modify caution.
code:
import sympy sympy.core.relational import relational mult_by_minus_one_map = { none: '==', '==': '==', 'eq': '==', '!=': '!=', '<>': '!=', 'ne': '!=', '>=': '<=', 'ge': '<=', '<=': '>=', 'le': '>=', '>': '<', 'gt': '<', '<': '>', 'lt': '>', } def move_inequality_constants(ineq, zero_on_right=false): l = ineq.lhs r = ineq.rhs op = ineq.rel_op all_on_left = l - r if zero_on_right: return relational(all_on_left, sympy.sympify(0), op) else: coeff_dict = all_on_left.as_coefficients_dict() var_types = coeff_dict.keys() new_rhs = sympy.sympify(0) s in var_types: if s == 1: all_on_left = all_on_left - coeff_dict[s] new_rhs = new_rhs - coeff_dict[s] if new_rhs < 0: all_on_left = all_on_left * -1 new_rhs = new_rhs * -1 op = mult_by_minus_one_map[op] return relational(all_on_left,new_rhs,op) # test code demo function below sympy.abc import x,y,z test_ineqs = [ x - 5 > y - z, x**2 + x - 5 > y + x**2 - z, x + 5 > y - z, x**3 + y**2 >= x + 5*y - z - 15] k in test_ineqs: print('re-arranging '+ str(k)) kn = move_inequality_constants(k) print('gives '+str(kn)) print('or equivalently ' + str(move_inequality_constants(k, true))) print('====')
output:
re-arranging x - 5 > y - z gives x - y + z > 5 or equivalently x - y + z - 5 > 0 ==== re-arranging x**2 + x - 5 > x**2 + y - z gives x - y + z > 5 or equivalently x - y + z - 5 > 0 ==== re-arranging x + 5 > y - z gives -x + y - z < 5 or equivalently x - y + z + 5 > 0 ==== re-arranging x**3 + y**2 >= x + 5*y - z - 15 gives -x**3 + x - y**2 + 5*y - z <= 15 or equivalently x**3 - x + y**2 - 5*y + z + 15 >= 0
Comments
Post a Comment